TEOR DE UMIDADE NA COLHEITA E REGULADOR DE CRESCIMENTO AFETANDO A PRODUTIVIDADE E A QUALIDADE DOS GRÃOS DE TRIGO - Souza, Allan Christian de (2014)
The wheat quality and yield may be limited or compromised by several factors in the field, being the climatic the main by factor at the end of the crop cycle. Aiming to determine whether different harvest time combined or not with plant growth regulator application affect crop yield and wheat grain quality, four experiments were conducted, differing by cultivars type and sowing time, at Ponta Grossa city, PR, in 2013. The experimental design used in the first time for both cultivars BRS-Pardela and Quartzo) were randomized blocks, at factorial scheme (2 x 5), with our without growth regulator applications and five grain moisture contents (30, 25, 20, 15 and 13%), being four replications. The experimental design for the second time for both cultivars were randomized blocks with five grain moisture content at harvest time (30, 25, 20, 15 and 13%) being 4 replications. For the first harvesting time the growth regulator application resulted in lower thousand grain weight only for cultivate BRS-Pardela and did not affect the yield, yield components as well the industrial quality for both wheat cultivars. The different harvesting times had no effect in either yield, Falling Number (FN) or hectoliter weight (PH) for both cultivars. In the second sowing time the production components and productivity for both cultivars were not affected by the different harvest time. A linear and quadratic decrease on the PH with the delaying of harvest time was noticed for BRS-Pardela and Quartz, respectively, for the FN only the BRS-Pardela showed quadratic reduction delaying the harvest time. Keywords: Triticum aestivum; No-tillage; harvest time; industrial quality, trinexapac-ethyl.